A model of foreign-born transfers: evidence from Canadian micro data - Don J. DeVoretz; Florin P. Vadean (Institute for the Study of Labor (IZA), 2005)
This paper models financial transfers outside the household for both the Canadian-born and foreign-born Canadian populations in a traditional expenditure framework. Using survey data we estimate transfer functions as part of a larger expenditure system and calculate Engel elasticities for remittances by both the Canadian and foreign-born populations. We conclude that transfers outside the household are a normal good for recent Asian immigrants and a luxury good for all other immigrants and Canadians. Immigrant transfers upon arrival are greater than Canadian-born transfers indicating a strong entry effect. Assimilation or convergence to the Canadian-born norm over time is however very slow. We also find evidence of negative foreign-born transfers as sending country households remit to Canadian immigrant households. Finally, all foreign-born groups generally consider remittances to charitable organizations a greater necessity than inter-household transfers.
Keywords: J63; O15; 330; immigration; remittances